2015
DOI: 10.2989/17280583.2015.1084310
|View full text |Cite
|
Sign up to set email alerts
|

Hazardous, harmful and dependent drinking in hostel-dwelling students at the University of the Free State, Bloemfontein: a cross-sectional study

Abstract: Follow-up studies are needed to confirm whether a significant difference in hazardous drinking of first year male students compared to seniors reflects the influence of university policy or merely precedes drinking acculturation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 20 publications
0
6
2
Order By: Relevance
“…Sample size was calculated using G*Power software to determine how many male and female students had to be included in the study to find a possible significant difference in hazardous drinking among male and female students from both universities 37 . For the study to be adequately powered, 155 men and 138 women had to be included, if sensitivity was 80% given the expected prevalence of 58.9% hazardous drinking among men at the UoA, 32.8% of hazardous drinking among male UKZN students, 45.3% prevalence of hazardous drinking among female students of the UoA and 18.9% hazardous drinking among female UKZN students 7 , 38 .…”
Section: Methodsmentioning
confidence: 99%
“…Sample size was calculated using G*Power software to determine how many male and female students had to be included in the study to find a possible significant difference in hazardous drinking among male and female students from both universities 37 . For the study to be adequately powered, 155 men and 138 women had to be included, if sensitivity was 80% given the expected prevalence of 58.9% hazardous drinking among men at the UoA, 32.8% of hazardous drinking among male UKZN students, 45.3% prevalence of hazardous drinking among female students of the UoA and 18.9% hazardous drinking among female UKZN students 7 , 38 .…”
Section: Methodsmentioning
confidence: 99%
“…Alcohol abuse among students nationally and internationally is rising and alcohol has generally been identified as the most commonly used substance among students (SA Statistics 2013;Van Zyl et al 2015). Hazardous drinking is defined by the volumes of alcohol consumed and/or the pattern of alcohol consumption associated with an increased risk for alcohol-attributable diseases in the future (Seggie 2012).…”
Section: Introduction Backgroundmentioning
confidence: 99%
“…This may include physical and/or psychological harm. A recent study by Van Zyl et al (2015) at the University of the Free State focusing on alcohol consumption among all undergraduate students in residences found that 15.6% of students partake in hazardous drinking, 4.1% of students partake in harmful drinking and 5.6% of students are alcohol dependent. This is in line with data reported by international studies (Johnston et al 2015).…”
Section: Introduction Backgroundmentioning
confidence: 99%
See 2 more Smart Citations